Pengaruh Bungkil Inti dan Lumpur Sawit yang Difermentasi dengan Aspergillus sp asal Akar Bambu terhadap Kandungan Lemak Ayam Broiler - Bambang Hartoyo; Supadmo Supadmo; Wihandoyo Wihandoyo; Ali Wibowo (Jurnal Agripet, 2015)
(The effect of palm kernel cake and palm oil sludge fermented with aspergillus sp derived from bamboo root on broilers fat content)ABSTRACT. The objective of this research was to determine the effect of palm kernel cake and palm oil sludge fermented with Aspergillus sp derived from bamboo root on broilers fat content including liver fat, abdominal fat and meat fat. Study was conducted for 8 weeks in Experimental Farm, Animal Science Faculty Jenderal Soedirman University, Purwokerto. Research utilized 196 male DOC strain Lohman, ration treatments, cage and other utilities. Seven allotted rations were R0 = control ration (without FPKC and FPOS), R1 = 7.5% FPKC, R2 = 15% FPKC, R3 = 22.5% FPKC, R4 = 7.5% FPOS, R5 = 15% FPOS, R6 = 22.5% FPOS. Each treatment unit used 7 (seven) DOCs with 4 (four) replicates. The obtained data were subject to analysis of variance followed by Orthogonal Contrasts. Result demonstrated that liver fat level was 1,79 3,86%, abdominal fat was 0,52 2,04%, and meat fat was 0,21 0,61%. Analysis of variance result showed that supplementing palm kernel cake and palm oil sludge fermented with Aspergillus sp derived from bamboo root highly significantly affected (P 0.01) abdominal fat level, significantly affected (P 0.05) liver fat level but did not significantly affected (P 0.05) broiler meat fat level.